Pengaruh Sistem Reward dan Punishment Terhadap Peningkatan Kualitas Pelayanan di Kantor BPJS Kesehatan - Rizal Ramli; Olgha S. Nusu (CV. Dalle’ Deceng Abeeayla, 2024)
This research aims to determine the influence of the reward and punishment system on improving service quality at the Gorontalo Province Health BPJS Office. The analytical method used is a quantitative method, with primary data sources and secondary data and uses a deductive approach. The population in this study were all employees of the BPJS Health Office of Gorontalo Province with a total of 42 respondents. The sampling technique used a saturated sampling technique. Based on the results of the analysis, it can be seen that the t count of the Reward Variable is obtained t count 5.419 > t table 1.682 and with a significance level of 0.000 < 0.05, so in this case the Ha1 hypothesis is accepted, which means that Rewards have a significant effect on improving the quality of service at the Gorontalo Province Health BPJS Office. Meanwhile, giving punishment has no significant effect on improving the quality of services at the Gorontalo Province BPJS Health Office. This is proven by the tcount of 0.311 which is smaller than the ttable value of 1.682 indicating a significance level value of 0.757 which is greater than 0.05, so the hypothesis (Ha2) is rejected. which means that the Punishment system has no significant effect on the level of Service Quality at the Gorontalo Province Health BPJS Office. Based on the results of the ANOVA test, the calculated F value was 10.535 with a significance level of 0.000.